Catalyst, preparation method and application in preparation of polyethylene and chlorinated polyethylene

By using dialkoxymagnesium support to prepare the catalyst, the problems of low chlorination rate and poor uniformity of chlorinated polyethylene in the prior art are solved, and high-performance preparation of high-density polyethylene and chlorinated polyethylene are achieved, thereby improving the chlorination uniformity and chlorination rate.

CN119552288AInactive Publication Date: 2025-03-04CHINA CHEM TECH RES INST

Patent Information

Application Number
CN202510135302.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the preparation of chlorinated polyethylene (CPE), the chlorination rate is low, the chlorination uniformity is poor, the residual crystallization is high, the aging is easy to aging and the environmental pollution is serious.

Method used

Using dialkoxymagnesium as a support, the particle size and morphology of the support are controlled by specific preparation methods, and a catalyst with high bulk density and narrow particle size distribution is prepared for the preparation of high-density polyethylene (HDPE) and CPE.

Benefits of technology

The high bulk density and narrow particle size distribution of high-density polyethylene are achieved, which improves the chlorination uniformity and chlorination rate of CPE, reduces production costs, and improves the performance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552288A_ABST
    Figure CN119552288A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst, a preparation method and application of the catalyst in preparation of polyethylene and chlorinated polyethylene. The catalyst carrier is synthesized under a low-temperature mild condition, the catalyst has high polymerization activity, strong hydrogen regulation sensitivity and good copolymerization performance, and the ethylene polymer with narrow particle size distribution of polymerization powder, high bulk density and excellent fluidity is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyethylene and relates to a catalyst, a preparation method and application in the preparation of polyethylene and chlorinated polyethylene. Background Art

[0002] Chlorinated Polyethylene (CPE) is made by reacting high-density polyethylene (HDPE) powder with chlorine. Since polar chlorine atoms are introduced into the polyethylene molecular structure and the chlorine atoms are randomly distributed along the polyethylene chain, the regularity of the original structure is destroyed, making the material have a certain elasticity. It is a new type of polymer elastomer material between rubber and plastic. This special molecular structure gives CPE good flexibility, weather resistance, ozone resistance, chemical corrosion resistance, cold resistance and flame retardancy, making it widely used in plastics, building materials, electrical, medicine, agriculture, rubber, paint, pigment, shipbuilding, papermaking, textiles, packaging and coatings.

[0003] The properties of chlorinated polyethylene are not only related to the chlorination process used, but also the structure and properties of the special HDPE resin play a vital role. Chlorinated polyethylene has the same carbon main chain structure as polyethylene resin. Its properties are related to the crystal regularity, molecular weight and distribution, molecular chain and branched chain structure, particle size and distribution, melt flow rate and S value of the resin raw material used, as well as the chlorine content, chlorination production method, etc.

[0004] In addition, the catalyst is also a key factor in determining the performance of chlorinated polyethylene, and the structure of the catalyst also determines the structure of polyethylene. PetroChina Liaoyang Petrochemical Company has developed a special material for chlorinated polyethylene, L0555P, which is very popular in the market. This special material is obtained by reacting ethoxymagnesium and titanium tetrachloride in a diluent at a certain temperature (Petroleum Technology Forum 2013 Issue 1·51). This catalyst is prepared without destroying the structure of ethoxymagnesium. The particle size of the obtained catalyst is much smaller than that of the carrier. The catalyst is characterized by a relatively rich pore structure, which makes the prepared chlorinated polyethylene powder have a relatively large pore volume, which is conducive to chlorination. However, the fine powder catalyst accounts for a large proportion, which has an impact on both HDPE and chlorinated polyethylene production.

[0005] CN102432726A reports the preparation of a catalyst specifically for chlorinated polyethylene. The catalyst uses magnesium chloride as a carrier, dissolves it in epichlorohydrin and alcohol, and then precipitates it with titanium tetrachloride to obtain the catalyst. The catalyst obtained by this method has a very small porosity, resulting in a wide distribution of polyethylene particles, mainly concentrated in 80-120 mesh and 140-200 mesh, and its particle size distribution index reaches 1.03, and the fine powder ( 200 mesh) reaches 13%. This fine particle size distribution is not conducive to the uniformity of chlorination.

[0006] Ethoxymagnesium is a two-dimensional network structure. After reacting with titanium tetrachloride, a small amount of ethoxy groups still exist, which makes the catalyst a network porous structure. Due to the replication of the ethylene polymerization catalyst, the prepared polyethylene is also a porous structure. This porous structure is very conducive to chlorination. Chlorinated polyethylene with uniform chlorination and a certain depth can be obtained.

[0007] In order to solve the problem of low activity of the original THB catalyst, PetroChina Liaoyang Petrochemical Company has developed a new chlorinated polyethylene catalyst (CN107840914B). The catalyst uses commercial magnesium ethoxide as a carrier, disperses the carrier magnesium ethoxide in an organic solvent C6~C13 straight-chain alkane, and adds a combination of alcohol ether compounds without active hydrogen and phthalic acid diester compounds as an electron donor during the catalyst preparation process. Titanium tetrachloride is added to react at 80°C to obtain the catalyst. Although its catalytic activity can reach 2×10 4 gPE / g.cat. However, the maximum bulk density of the obtained polyethylene is only 0.34 g / cm 3 . Not very practical.

[0008] CN102432726 uses magnesium dichloride as a carrier, dissolves it in a mixture of toluene, epichlorohydrin, tributyl phosphate and ethanol, and treats it with diethylaluminum monochloride and titanium tetrachloride respectively to obtain a solid catalyst. This catalyst was used to produce chlorinated polyethylene material on an industrial device of Mitsui CX process, and the maximum bulk density of the obtained polyethylene was only 0.4g.cm 3 , the particle size distribution is relatively wide, 180 m accounts for 25~38%, 106 m accounts for 42~58%, fine powder ( 75 m), accounting for 8~14%. A large amount of fine powder is not conducive to chlorination. The pore size of polyethylene measured by mercury intrusion method is 7~20nm. The pore size is small and the distribution is wide, which is also not conducive to chlorination reaction. The patent only reports the chlorination rate, not the performance of chlorinated polyethylene.

[0009] At present, the high-density polyethylene resin used for preparing chlorinated polyethylene (CPE) is mainly produced by slurry polymerization process. The produced polyethylene resin has the problems of wide particle size distribution, large particles and ultrafine powder, and high oligomer content. Therefore, it is generally necessary to screen to remove large particles during the production process, but there are still a lot of ultrafine powders. Since it contains a lot of oligomers, it is easy to cause the performance of the final CPE resin to decrease. In addition, the xylene residual value in the CPE product generated by chlorination of such polyethylene resin is usually high, indicating that the uniformity of CPE is poor, which will directly affect the performance of CPE resin. Therefore, there is an urgent need for a polyethylene resin that is more suitable for CPE production. Summary of the invention

[0010] The present invention provides a dialkoxy magnesium carrier having a particle size of 3.5 to 10.0 m, and / or, spherical or quasi-spherical.

[0011] According to an embodiment of the present invention, the dialkoxy magnesium carrier is prepared by the following method: In the presence of an initiator, magnesium and alcohol react at a temperature T, 30°C ≤ T ≤ 60°C to obtain the product.

[0012] The present invention also provides a method for preparing the above-mentioned dialkoxy magnesium carrier, comprising: in the presence of an initiator, magnesium and alcohol react at a temperature T, 30°C≤T≤60°C to obtain the dialkoxy magnesium carrier.

[0013] According to the embodiment of the present invention, there is no particular restriction on the shape and particle size of magnesium. For example, magnesium powder with a particle size of 50 to 200 m.

[0014] According to an embodiment of the present invention, the alcohol is selected from fatty alcohols represented by the general formula R-OH, where R represents C 1-6 Alkyl; for example, alcohol is selected from one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, n-pentanol, isopentanol, neopentyl alcohol, cyclopentanol and cyclohexanol, and in the exemplary embodiment is ethanol.

[0015] According to an embodiment of the present invention, the weight ratio of the alcohol to magnesium is (8-30):1, preferably (10-20):1, such as 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, 25:1. When the weight ratio is less than 8:1, the viscosity of the slurry increases rapidly; and when the weight ratio is more than 30:1, the bulk density of the dialkoxy magnesium carrier decreases. In addition, the ratio of alcohol to magnesium also affects the particle size of the carrier. The lower the ratio, the smaller the particle size.

[0016] According to an embodiment of the present invention, the initiator is selected from N-chlorosuccinimide, N-bromosuccinimide or I2.

[0017] According to an embodiment of the present invention, the weight ratio of the initiator to magnesium is (0.005-0.3):1, such as 0.01:1, 0.05:1, 0.1:1, 0.2:1. When it is less than 0.005:1, the reaction rate becomes too slow; and when it is more than 0.3:1, the size of the generated particles becomes uneven, and too many fine particles stick together.

[0018] The inventors found that the reaction temperature has a great influence on the particle size of the dialkoxy magnesium carrier. The lower the temperature, the smaller the particle size. The temperature T is preferably 40-60°C.

[0019] According to an embodiment of the present invention, the reaction time is 3 to 12 hours, preferably 4 to 8 hours. The inventors have found that increasing the temperature will cause the particles to become larger or uneven, so the present invention does not need to increase the temperature for aging. The carrier particles can be aged by a certain reaction time (i.e., aging time).

[0020] According to an embodiment of the present invention, the reaction is carried out under stirring, for example, the stirring rate is 200-1500 rpm, preferably 300-1200 rpm, for example 600 rpm, 800 rpm, 1000 rpm, 1100 rpm. When the stirring rate exceeds the above range, the problem of irregular particle distribution will occur.

[0021] According to an embodiment of the present invention, the reaction is carried out under an inert environment, such as a nitrogen atmosphere.

[0022] According to an embodiment of the present invention, the method for preparing the dialkoxy magnesium carrier comprises: In an inert environment, the alcohol and the initiator are stirred and mixed, and heated to a temperature T. After the initiator is dissolved, magnesium powder is added to react to obtain the dialkoxy magnesium carrier.

[0023] The present invention also provides the use of the dialkoxy magnesium carrier in the preparation of catalysts, HDPE and CPE.

[0024] According to an embodiment of the present invention, the catalyst, HDPE and CPE have the definitions shown below.

[0025] The present invention also provides a catalyst, comprising the above-mentioned dialkoxy magnesium carrier.

[0026] According to an embodiment of the present invention, the particle size of the catalyst is 3.0 to 10.0 m, e.g. 3.5~6.0 m; and / or, the catalyst is spherical or quasi-spherical.

[0027] According to an embodiment of the present invention, the catalyst is obtained by contact reaction of the dialkoxy magnesium support, a titanium halide compound and an internal electron donor.

[0028] According to an embodiment of the present invention, the catalyst contains, by weight percentage, 20 to 30 wt % of magnesium, 1 to 10 wt % of titanium, 5 to 20 wt % of electron donors and 40 to 70 wt % of halogen atoms.

[0029] The present invention also provides a method for preparing the above catalyst, comprising contacting the dialkoxy magnesium support, titanium halide and an internal electron donor; Preferably, the preparation method comprises: (1) first reacting the dialkoxy magnesium support and titanium halide in an organic solvent to generate a halogen-substituted alkoxy group of the dialkoxy magnesium; (2) After step (1) is completed, an internal electron donor is added to the system and the temperature is raised to react to obtain the catalyst.

[0030] According to an embodiment of the present invention, the titanium halide may be selected from titanium halides known in the art, such as titanium tetrachloride.

[0031] According to an embodiment of the present invention, relative to 1 mol of dialkoxymagnesium, the amount of the titanium halide is 0.1-10 mol, such as 0.3-8 mol or 0.5-5 mol, exemplified by 1 mol, 2 mol, 3 mol, 4 mol.

[0032] According to an embodiment of the present invention, the organic solvent may be selected from C 6-12 (saturated) aliphatic or aromatic hydrocarbons, preferably C 7-10 Saturated aliphatic hydrocarbons or aromatic hydrocarbons, for example, one or more selected from octane, nonane, decane, toluene and xylene.

[0033] According to an embodiment of the present invention, the internal electron donor may preferably be an alkoxy silicon compound having a structure shown in Formula I, R' n Si(OR'') 4n’ Formula I Wherein, R' and R'' are the same or different and are independently selected from C 1~12 The hydrocarbon group; n and n' are the same or different and are independently selected from natural numbers of 1 to 3, for example, 1, 2 or 3; For example, the hydrocarbon group includes alkyl, cycloalkyl, alkenyl, phenyl, alkyloxy, haloalkyl, halocycloalkyl, haloalkenyl, halophenyl, haloalkyloxy; Preferably, said R' and R'' are the same or different and are independently selected from C1~4 Alkyl, C 3~8 Cycloalkyl, C 2~6 Alkenyl, C 6~12 Phenyl, C 1~4 Alkyloxy, C 1~4 Haloalkyl, C 3~8 Halogenated cycloalkyl, C 2~6 Halogenated alkenyl, C 6~12 Halogenated phenyl, C 1~4 haloalkyloxy; In some embodiments, R' and R" are the same or different and are independently selected from methyl, ethyl, propyl, isopropyl, butyl, isobutyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, phenyl, vinyl, γ-chloropropyl, methoxy, and ethoxy.

[0034] Exemplarily, the internal electron donor is selected from dimethyldimethoxysilane, dipropyldimethoxysilane, diisopropyldimethoxysilane, isobutyldimethoxysilane, dibutyldimethoxysilane, cyclohexylmethyldimethoxysilane, cyclohexylisopropyldimethoxysilane, cyclopentylisobutyldimethoxysilane, cyclopentylisopropyldimethoxysilane, cyclopentylbutyldimethoxysilane, cyclopentylpropyldimethoxysilane, dicyclopentyldimethoxysilane, diphenyldimethoxysilane, phenyltrimethoxysilane, methyltrimethoxysilane, butyltrimethoxysilane, isobutyltrimethoxysilane, γ-chloropropyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrioxysilane, dimethyldimethoxysilane, One or more of ethoxysilane, dipropyldiethoxysilane, diisopropyldiethoxysilane, isobutyldiethoxysilane, dibutyldiethoxysilane, cyclohexylmethyldiethoxysilane, cyclohexylisopropyldiethoxysilane, cyclopentylisobutyldiethoxysilane, cyclopentylisopropyldiethoxysilane, cyclopentylbutyldiethoxysilane, cyclopentylpropyldiethoxysilane, dicyclopentyldiethoxysilane, diphenyldiethoxysilane, phenyltriethoxysilane, methyltriethoxysilane, butyltriethylsilane, isobutyltriethoxysilane, γ-chloropropyltriethoxysilane, vinyltriethoxysilane, vinyltrimethoxysilane, tetramethoxysilane and tetraethoxysilane.

[0035] According to an embodiment of the present invention, the amount of the internal electron donor is 0.05-1.0 mol, for example 0.1-0.5 mol, relative to 1 mol of magnesium. When the amount of the internal electron donor used exceeds the preferred range, there may be a problem of reduced polymerization activity of the generated catalyst.

[0036] According to an embodiment of the present invention, in step (1), the dialkoxy magnesium support and the organic solvent are first mixed and stirred, cooled to -20 to 10°C, titanium halide is added thereto, and then the temperature is raised to 60 to 80°C; Preferably, the titanium halide is added in a dropwise manner, for example, the dropwise addition is completed over 30 minutes to 2 hours; Preferably, the temperature is raised by programmed temperature rise, and the programmed temperature rise is from 1.0 to 2.0 hours to 60 to 80°C.

[0037] The reaction of the dialkoxymagnesium support with the titanium halide at low temperature in a state of being suspended in an organic solvent may cause a problem of generating a large amount of fine particles and adhering particles outside these reaction temperature ranges due to the destruction of the support particle shape.

[0038] According to an embodiment of the present invention, the temperature when the internal electron donor is added to the system in step (2) is 60-80°C.

[0039] According to an embodiment of the present invention, in step (2), the temperature is raised to 100-120° C. and the reaction is carried out for 1-3 hours.

[0040] According to an embodiment of the present invention, the preparation method further comprises post-treatment. After the reaction in step (2) is completed, the solid catalyst is filtered out by heat, washed with n-decane and n-hexane respectively until the filtrate is substantially colorless, and dried to obtain a solid.

[0041] The present invention also provides a catalyst system, comprising: a) the aforementioned catalyst; b) a cocatalyst, which is a metal organic compound, preferably an organoaluminum compound R''' 3-m A1X m , where X is halogen and R''' is C 1~12 Alkyl (e.g. C 1~6 The alkyl group is exemplified by methyl, ethyl, propyl, isopropyl, butyl, and isobutyl), and m is an integer of 0 to 2.

[0042] According to an embodiment of the present invention, the molar ratio of aluminum in the co-catalyst to titanium in the catalyst active component is 10-300, preferably 10-150, more preferably 30-100.

[0043] In some embodiments, the R''' is ethyl, m=0, that is, the co-catalyst is triethylaluminum.

[0044] The present invention also provides the use of the catalyst and catalyst system in the preparation of HDPE and CPE.

[0045] According to an embodiment of the present invention, the HDPE and CPE have the definitions shown below.

[0046] The present invention also provides a method for preparing HDPE, comprising: C3~8The above-mentioned dialkoxy magnesium support, catalyst and / or catalyst system are used in the α-olefin polymerization process.

[0047] According to an embodiment of the present invention, the C 3~8 The α-olefin is selected from one or more of propylene, butene-1, 4-methylpentene-1, hexene-1, octene-1, styrene and the like.

[0048] According to an embodiment of the present invention, the C 3~8 The α-olefins account for 0.1~1wt% of the total ethylene.

[0049] According to an embodiment of the present invention, the polymerization reaction temperature is 30-90° C., preferably 40-80° C.; the polymerization reaction pressure is 0.1-1.0 MPa, preferably 0.2-0.8 MPa.

[0050] According to an embodiment of the present invention, the HDPE has one or more of the following parameters, preferably has both (6) and (7): (1) Density: 0.930~0.960g / cm 3 , for example 0.950~0.960g / cm 3 or 0.945~0.956g / cm 3 ; (2) melt mass flow rate (MFR5.0) is 0.2 to 2.0 g / 10 min, for example, 0.3 to 1.0 g / 10 min; (3) S value (melt flow ratio) is 10 to 20; (4) Particle size is 100 to 300 microns; (5) Melting point not less than 132°C; (6) Bulk density ≥ 0.36 g / cm 3 , preferably ≥0.39g / cm 3 , for example, 0.36~0.46g / cm 3 ; (7) Particle size distribution (D 90 -D 10 ) / D 50 )<0.8, for example, 0.6-0.7, preferably <0.6; (8) Aperture 300-800 nm, for example, 400-700 nm; (9) Greater than 425 m large particle powder content is less than 1wt%, less than 63 The content of ultrafine powder of m is less than 1wt%, 75-425 The powder content between m is greater than 98wt%.

[0051] The polyethylene has a high bulk density and a good pore size and volume distribution. The micropores in the particles are mainly concentrated at 700 nm. This pore size is very conducive to the chlorination reaction and can increase the chlorine content of the CPE resin.

[0052] Polyethylene resin with narrow particle size distribution is conducive to improving the chlorination uniformity of CPE resin, and the characteristics of large particles and low ultrafine powder content are conducive to improving the yield of CPE resin and reducing production costs.

[0053] The present invention also provides a HDPE having one or more of the following parameters, preferably having both (6) and (7): (1) Density: 0.930~0.960g / cm 3 , preferably 0.950~0.960g / cm 3 ; (2) melt mass flow rate (MFR5.0) is 0.2 to 2.0 g / 10 min, for example, 0.3 to 1.0 g / 10 min; (3) S value (melt flow ratio) is 10 to 20; (4) Particle size is 100 to 300 microns; (5) Melting point not less than 132°C; (6) Bulk density ≥ 0.36 g / cm 3 , preferably ≥0.39g / cm 3 , for example, 0.36~0.46g / cm 3 ; (7) Particle size distribution (D 90 -D 10 ) / D 50 )<0.8, preferably<0.7, for example, 0.6~0.7; (8) Greater than 425 The content of large particle powder of m is less than 1wt%, less than 63 The content of ultrafine powder of m is less than 1wt%, 75-425 The powder content between m is greater than 98wt%; Preferably, the HDPE is prepared by the above method.

[0054] The present invention also provides the use of the above HDPE in the preparation of CPE, and a method for preparing CPE, which is prepared from the above HDPE.

[0055] Definition and explanation of terms A quasi-spherical structure is a three-dimensional granular structure that is spherical in main body but has an irregular concave-convex structure on the surface, resulting in a slight difference from a sphere. This is a conventional term in the art. Preferably, the three-dimensional granular structure has a diameter ratio of 1:(0.7-1.5):(0.7-1.5) in the longitudinal, transverse and vertical directions; or it can be judged by sphericity, which is equal to the ratio of the surface area of ​​a sphere of the same volume as the object to the surface area of ​​the object. The closer the particle is to a sphere in appearance, the closer its sphericity is to 1; for example, 0.5<sphericity<1 is considered to be a quasi-spherical structure, and preferably 0.6≤sphericity<1, 0.7≤sphericity<1, 0.8≤sphericity<1, and 0.9≤sphericity<1.

[0056] Beneficial Effects The present invention aims at the problems existing in the current chlorinated polyethylene raw material powder, and provides a method for preparing a polyethylene special resin, the prepared polyethylene special resin, the application thereof, and a method for preparing a catalyst and a carrier thereof used in the preparation of the polyethylene special resin, so as to solve the technical problems of low chlorination rate, poor chlorination uniformity, high residual crystallinity, easy aging, serious environmental pollution, etc. of the chlorinated polyethylene produced by the prior art.

[0057] The catalyst carrier of the present invention can be synthesized under low temperature and mild conditions. The obtained catalyst has high polymerization activity, strong hydrogen regulation sensitivity, and good copolymerization performance. The obtained polymer powder has a narrow particle size distribution, high bulk density, and excellent fluidity of ethylene polymer.

[0058] Due to the porous network structure of ethoxy magnesium, it is very suitable for preparing porous polyethylene. The present invention uses ethoxy magnesium as a carrier to prepare a catalyst. In the process of preparing ethoxy magnesium, the inventor surprisingly found that by changing the amount of ethanol and the reaction temperature, the particle size and morphology of the carrier can be controlled. The particle size of the carrier can be controlled within a range of 3.5 to 10.0 m, and the morphology is spherical or quasi-spherical. The polyethylene obtained by the catalyst prepared by this method is spherical or quasi-spherical, so the bulk density is very high, and the laboratory scale can reach 0.40g / cm 3 Above, industrial production can reach 0.45 g / cm 3 This is the highest bulk density of high-density polyethylene so far. Not only is the bulk density high, but the particle size distribution is also very narrow, with a particle size distribution below 0.7. This kind of polyethylene is very suitable for the preparation of chlorinated polyethylene.

[0059] The inventors also found that the particle size of polyethylene has an important influence on the performance of CPE. The polyethylene raw material used for CPE is polyethylene powder, and the size of the polyethylene powder particle size has a significant effect on the particle uniformity of the chlorinated product. If the particle size is smaller, the specific surface area of ​​the particles is larger, the chlorine atoms can easily penetrate into the interior of the particles, and the chlorination is more uniform. However, the polyethylene particles cannot be too fine, and fine particles will increase the free energy of their surface and increase the tendency of particles to condense, which is not conducive to the dispersion of the resin. If the particle size is larger, it is difficult for chlorine atoms to penetrate into the interior of the particles, and the chlorination is uneven. Therefore, the particle size distribution of the polyethylene resin raw material is required to be as concentrated as possible. The polyethylene particle size prepared by the present invention is concentrated in the range of 160-190μm, and there are very few large particles greater than 425μm and less than 43μm. Such a particle size is conducive to improving the yield of CPE and reducing production costs.

[0060] In addition, the microporous structure of polyethylene also has a very important influence on chlorination. The larger the pore size and pore volume, the more conducive it is for chlorine to enter the interior of the polyethylene particles, making the chlorination rate higher and more uniform. The polyethylene micropores prepared by the present invention are 300-800nm, which are macropores, and are conducive to improving the chlorination rate and uniformity. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is an electron microscope image of the carrier obtained in Carrier Preparation Example 1; Figure 2 This is an electron microscope image of the catalyst obtained in Preparation Catalyst Example 1; Figure 3 and Figure 4 This is an electron microscope image of polyethylene obtained from an industrial production example. DETAILED DESCRIPTION

[0062] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0063] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0064] Polymer property determination: Melt flow index (MI): According to ASTM-D1238 standard method, the measurement temperature is 190°C, and the measurement load is 5.0kg and 21.6kg.

[0065] Determination of polymer density: The density of plastics was determined according to the standard test method for density gradient method (ASTM 1505-03).

[0066] The apparent density is determined by ASTM-D-1895 method.

[0067] The screening is determined by GB / T19077-2016 method.

[0068] The particle size of polyethylene was determined by a laser particle analyzer (Mastersizer X, Malvern). 10 , D 50 and D 90 The distribution refers to the size of the particles at each percentage of 10, 50 and 90. 50 is defined as the average particle distribution, and the particle size distribution is defined as (D 90 -D 10 ) / D 50 .

[0069] The weight-average molecular weight and molecular weight distribution of the polymer were obtained by high-temperature GPC-IR testing.

[0070] S value: melt flow ratio, that is, the ratio of MFR (melt mass flow rate) measured under the test conditions of 190°C, 21.6 kg weight and 5 kg weight.

[0071] Description of the performance test method of chlorinated polyethylene: Chlorine content / %: refer to method B in GB / T 7139-2002.

[0072] Mooney viscosity: refer to GB / T 1232.12000.

[0073] Shore hardness: refer to GB / T531.12008.

[0074] Tensile strength: refer to GB / T 528-2009, using I-type dumbbell cutter.

[0075] Elongation at break: refer to GB / T 1340.12006.

[0076] The particle size of the magnesium powder in carrier preparation examples 1 to 7 and carrier preparation comparative example 1 is 50 to 200 m.

[0077] Carrier Preparation Example 1 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1000rpm. After heating to 40°C and stirring for 5min, NCS was fully dissolved. 6g of magnesium powder was added thereto, and the reaction was carried out for 8 hours until the reaction liquid turned grayish white and no hydrogen was generated. The reaction liquid was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white solid, which was a dialkoxymagnesium (Mg(OEt)2) carrier. Figure 1 The electron microscope shown shows that the carrier particle size is 4.5 μm and is spherical.

[0078] Carrier Preparation Example 2 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1200rpm. After heating to 40°C and stirring for 5min, NCS was fully dissolved. 6g of magnesium powder was added thereto, and the reaction was carried out for 8 hours until the reaction liquid became off-white and no hydrogen was generated. The solid was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white solid, which was a dialkoxy magnesium carrier. Electron microscopy showed that the carrier particle size was 3.5μm and was spherical.

[0079] Carrier Preparation Example 3 To a 500ml reactor replaced with nitrogen, 200mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1000rpm. After heating to 40°C and stirring for 5min, NCS was fully dissolved. 6g of magnesium powder was added thereto, and the reaction was carried out for 8 hours until the reaction liquid became off-white and no hydrogen was generated. The reaction liquid was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white solid, which was a dialkoxy magnesium carrier. Electron microscopy showed that the carrier particle size was 5.0μm and was spherical.

[0080] Carrier Preparation Example 4 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1200rpm. After heating to 50°C and stirring for 5min, NCS was fully dissolved. 6g of magnesium powder was added thereto, and the reaction was carried out for 8 hours until the reaction liquid became off-white and no hydrogen was generated. The solid was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white solid, which was a dialkoxy magnesium carrier. Electron microscopy showed that the carrier particle size was 4.0μm and was spherical.

[0081] Carrier Preparation Example 5 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1200rpm. After heating to 60°C and stirring for 5min, NCS was fully dissolved. 6g of magnesium powder was added thereto, and the reaction was carried out for 8 hours until the reaction liquid became off-white and no hydrogen was generated. The solid was filtered, washed with n-hexane and dried to obtain a white solid, which was a dialkoxy magnesium carrier. Electron microscopy showed that the carrier particle size was 6.5μm and was spherical.

[0082] Carrier Preparation Example 6 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.03g of I2 were added in sequence, the stirring speed was 1200rpm, and the mixture was heated to 50°C and stirred for 5min to fully dissolve I2. 6g of magnesium powder was added thereto, and the mixture was reacted for 8 hours until the reaction liquid became off-white and no hydrogen was generated. The reaction mixture was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white solid, which was a dialkoxymagnesium carrier. Electron microscopy showed that the carrier particle size was 5.0μm and was spherical.

[0083] Carrier Preparation Example 7 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1000rpm. After heating to 40°C, the mixture was stirred for 5min to fully dissolve the NCS. 6g of magnesium powder was added thereto, and the mixture was reacted for 4 hours until the reaction liquid became off-white and no hydrogen was generated. The reaction liquid was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white carrier. Electron microscopy showed that the carrier particle size was 5.2μm and was spherical.

[0084] Carrier Preparation Comparative Example 1 To a 500ml reactor replaced with nitrogen, 100mL of anhydrous ethanol and 0.045g of N-chlorosuccinimide (NCS) were added in sequence, with a stirring speed of 1000rpm. After heating to 80°C and stirring for 5min, NCS was fully dissolved. 6g of magnesium powder was added thereto, and the reaction was carried out for 8 hours until the reaction liquid became off-white and no hydrogen was generated. The reaction liquid was filtered, and the obtained solid was washed with n-hexane and dried to obtain a white solid, which was a dialkoxy magnesium carrier. Electron microscopy showed that the carrier particle size was 10.5μm and irregular in shape.

[0085] Preparation of Catalyst Example 1 7.5 g of active Mg(OEt)2 carrier (carrier preparation example 1) and 200 mL of toluene (dried by 4A molecular sieve) were added to a 500 ml reactor replaced with nitrogen. The stirring speed was 300 rpm. The temperature was first cooled to -10 °C, and 15 mL of titanium tetrachloride was added dropwise. After the addition was completed, the temperature was raised to 70 °C. At this temperature, 2 ml of γ-chloropropyltriethoxysilane electron donor was added. The temperature was continued to rise to 110 °C for 120 minutes to obtain a solid. After the reaction was completed, the solid was filtered out hot and washed 4 times with n-decane and n-hexane, 200 mL each time, until the filtrate was basically colorless. After drying, a solid catalyst was obtained. The titanium content of the catalyst obtained in this way was 7.5 wt%. Electron microscopy showed that the catalyst particle size was 4.5 μm and was spherical (see Figure 2 ).

[0086] Preparation of Catalyst Example 2 7.5g of active Mg(OEt)2 carrier (carrier preparation example 1) and 200mL toluene (dried by 4A molecular sieve) were added to a 500ml reactor replaced with nitrogen. The stirring speed was 300rpm. The temperature was first cooled to -10°C, and 15mL of titanium tetrachloride was added thereto. After the addition was completed, the temperature was raised to 70°C. At this temperature, 2ml of γ-chloropropyltrimethoxysilane electron donor was added, and the temperature was continued to rise to 110°C for 120 minutes to obtain a solid. After the reaction was completed, the solid was filtered out hot, washed with n-decane and n-hexane 4 times, 200mL each time, until the filtrate was basically colorless, and dried to obtain a solid catalyst. The titanium content of the catalyst obtained was 5.5wt%. Electron microscopy showed that the catalyst particle size was 4.4μm, which was spherical.

[0087] Preparation of Catalyst Example 3 7.5 g of active Mg(OEt)2 carrier (carrier preparation example 1) and 200 mL of toluene (dried with 4A molecular sieve) were added to a 500 ml reactor replaced with nitrogen. The stirring speed was 300 rpm. The temperature was first cooled to -10 °C, and 15 mL of titanium tetrachloride was added thereto. After the addition was completed, the temperature was raised to 70 °C. At this temperature, 2 ml of γ-chloropropyltrimethoxysilane and γ-chloropropyltriethoxysilane electron donor mixture (molar ratio 3:7) was added. The temperature was continued to rise to 110 °C for 120 minutes to obtain a solid. After the reaction was completed, the solid was filtered out hot, washed with n-decane and n-hexane 4 times, 200 mL each time, until the filtrate was basically colorless, and dried to obtain a solid catalyst. The titanium content of the catalyst obtained was 6.2 wt%. Electron microscopy showed that the catalyst particle size was 4.6 μm, which was spherical.

[0088] Preparation of Catalyst Example 4 The same method as Example 1 for preparing the catalyst was used, except that the titanium dropping temperature was changed to -20°C. The titanium content of the catalyst thus obtained was 5.8 wt%. The electron microscope showed that the catalyst particle size was 4.6 μm. Preparation of Catalyst Example 5 The same method as Example 1 was used to prepare the catalyst, except that the amount of titanium tetrachloride was changed to 35 mL. The titanium content of the catalyst thus obtained was 8.6 wt %. Electron microscopy showed that the catalyst particle size was 4.8 μm.

[0089] Preparation of Catalyst Example 6 The same method as Example 1 was used to prepare the catalyst, except that the stirring speed was increased to 1000 rpm, and the titanium content of the catalyst obtained was 4.8 wt %. The electron microscope showed that the catalyst particle size was 4.3 μm.

[0090] Preparation of Catalyst Example 7 The same method as Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Example 2. The titanium content of the catalyst thus obtained was 8.0 wt %. Electron microscopy showed that the catalyst particle size was 3.5 μm.

[0091] Preparation of Catalyst Example 8 The same method as in Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Example 3. The titanium content of the catalyst thus obtained was 7.6 wt %. Electron microscopy showed that the catalyst particle size was 5.0 μm.

[0092] Preparation of Catalyst Example 9 The same method as in Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Example 4. The titanium content of the catalyst thus obtained was 6.1 wt %. Electron microscopy showed that the catalyst particle size was 4.0 μm.

[0093] Preparation of Catalyst Example 10 The same method as in Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Example 5. The titanium content of the catalyst thus obtained was 5.2 wt %. The particle size of the catalyst under electron microscopy was 6.5 μm.

[0094] Preparation of Catalyst Example 11 The same method as in Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Example 6. The titanium content of the catalyst thus obtained was 5.4 wt %. Electron microscopy showed that the catalyst particle size was 5.0 μm.

[0095] Preparation of Catalyst Example 12 The same method as in Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Example 7. The titanium content of the catalyst thus obtained was 5.3 wt %. Electron microscopy showed that the catalyst particle size was 5.2 μm.

[0096] Preparation of comparative catalyst example 1 The same method as Example 1 was used to prepare the catalyst, except that the carrier was replaced with the active Mg(OEt)2 carrier obtained in Comparative Example 1. The titanium content of the catalyst thus obtained was 7.2 wt %. Electron microscopy showed that the catalyst particle size was 10.5 μm.

[0097] Polymerization Example 1 Add 5.5 liters of dehydrated hexane and a hexane solution of triethylaluminum (at an Al / Ti molar ratio of 30) to a 10-liter slurry reactor in sequence, start stirring at a stirring speed of 1000 rpm, add 20 mg of the catalyst prepared in Example 1 of the catalyst preparation method to the slurry reactor, and add hexene-1 at a mass ratio of ethylene to hexene-1 of 600:1. Heat to 50°C. Continuously add ethylene and hydrogen to the slurry reactor, the mass ratio of ethylene to hydrogen is 6000:1, and the temperature in the reactor reaches 83°C and the pressure reaches 0.6MPa; during the polymerization reaction, the pressure in the reactor is maintained relatively stable by the introduction of ethylene. When the amount of ethylene polymerization reaches 1200g, the polymerization reaction is terminated. After the polymerization is completed, the pressure in the slurry reactor is vented, and the temperature in the slurry reactor is lowered to room temperature by circulating water in the reactor jacket, and the polyethylene resin powder for chlorinated polyethylene is obtained by discharging. After the reactor is disassembled, the polymerization reactor is clean and there is no polyethylene particle sticking to the wall. The polymer is spherical. The polymerized products were tested for bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution, etc. The results are shown in Tables 1 and 2 for details.

[0098] Polymerization Example 2 The same as the polymerization example 1, except that the mass ratio of ethylene to hydrogen is 4000:1, the mass ratio of α-olefin to ethylene is 400:1, and the α-olefin is hexene-1. After the polymerization, the polymerization kettle is clean after the kettle is dismantled, and there is no polyethylene particle sticking to the wall. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are measured, and the results are detailed in Table 1 and Table 2.

[0099] Polymerization Example 3 The same as polymerization example 1, except that the mass ratio of ethylene to hydrogen is 2000:1, the mass ratio of α-olefin to ethylene is 200:1, and the α-olefin is hexene-1. After the polymerization is completed, the polymerization kettle is clean after the kettle is dismantled, and there is no polyethylene particle sticking to the wall. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are shown in Tables 1 and 2 for details.

[0100] Polymerization Example 4 The same as polymerization example 1, except that the mass ratio of ethylene to hydrogen is 6000:1, the mass ratio of α-olefin to ethylene is 600:1, and the α-olefin is butene-1. After the polymerization is completed, the polymerization kettle is clean after the kettle is dismantled, and there is no polyethylene particle sticking to the wall. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are shown in Tables 1 and 2 for details.

[0101] Polymerization Example 5 The same as the polymerization example 1, except that the mass ratio of ethylene to hydrogen is 6000:1, the mass ratio of α-olefin to ethylene is 600:1, and the α-olefin is propylene-1. After the polymerization is completed, the polymerization kettle is clean after the kettle is dismantled, and there is no polyethylene particle sticking to the wall. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are shown in Tables 1 and 2 for details.

[0102] Polymerization Example 6 The same as in Polymerization Example 1, except that the mass ratio of ethylene to hydrogen is 4000:1, the mass ratio of α-olefin to ethylene is 400:1, and the α-olefin is propylene-1. After the polymerization is completed, the polymerization kettle is clean after the kettle is disassembled, and there is no polyethylene particle sticking to the wall. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are shown in Tables 1 and 2 for details.

[0103] Polymerization Example 7 The same as polymerization example 1, except that the mass ratio of ethylene to hydrogen was 6000:1, and no α-olefin was added. After the polymerization was completed, the polymerization kettle was clean after the kettle was dismantled, and there was no polyethylene particle sticking to the wall. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are shown in Tables 1 and 2 for details.

[0104] Polymerization Examples 8 to 18 The same as polymerization example 1, except that the catalysts are respectively prepared from catalyst examples 2 to 12. The bulk density, melt index, weight average molecular weight and molecular weight distribution, average particle size and particle size distribution of the polymerized product are shown in Tables 1 and 2 for details.

[0105] Comparative Polymerization Example 1 The same as in Polymerization Example 1, except that the catalyst is the catalyst obtained in Preparation Comparative Catalyst Example 1. The polymerized product was subjected to bulk density measurement, melt index, weight average molecular weight measurement and molecular weight distribution, average particle size measurement and particle size distribution, etc., and the results are detailed in Tables 1 and 2.

[0106] Table 1

[0107] Table 2

[0108] From the above examples and the data in Tables 1 and 2, it can be found that the particle size of the dialkoxy magnesium carrier can be controlled by controlling the reaction temperature, the amount of ethanol, the activation time, and the stirring speed; for example, the lower the reaction temperature, the smaller the particle size; the greater the amount of ethanol, the larger the particle size; the longer the activation time is conducive to a smaller particle size; and the higher the stirring speed, the smaller the particle size.

[0109] The catalyst of the present invention has high catalytic activity. The reference document CN102432726 requires an ethylene / hydrogen molar ratio of 5 to 2.5 to increase the melt index to about 0.4, while the present invention only requires a mass ratio of 6000:1 (converted molar ratio is 400:1), showing strong hydrogen adjustment sensitivity. In addition, the polyethylene prepared by the catalyst of the present invention has a high bulk density and a narrow particle size distribution, which is very conducive to chlorination.

[0110] Industrial production example (I) Preparation of polyethylene resin powder for chlorinated polyethylene To 12m 3 7.0 ml of dehydrated hexane was added into the slurry reactor. 3 , a hexane solution of triethylaluminum (according to an Al / Ti molar ratio of 30), start stirring at a stirring speed of 200rpm, add 60g of the catalyst obtained in Example 7 for preparing the catalyst into the slurry reactor, and heat to 50°C. According to the mass ratio of ethylene to propylene-1 of 600:1 and the mass ratio of ethylene to hydrogen of 6000:1, ethylene, propylene-1 and hydrogen are continuously added to the slurry reactor, and the temperature in the reactor is made to reach 83°C and the pressure is made to reach 0.6MPa; during the polymerization reaction, the pressure in the reactor is maintained relatively stable by the introduction of ethylene. When the amount of ethylene polymerization reaches 2500kg, the polymerization reaction is terminated. After the polymerization is completed, the pressure in the slurry reactor is vented, and the temperature in the slurry reactor is lowered to room temperature through the circulating water in the reactor jacket, and the polyethylene resin powder dedicated to chlorinated polyethylene is obtained by discharging the material. Through the sight glass, the polymerization reactor is observed to be clean and there is no polyethylene particle sticking to the wall. The polymer is spherical (see Figure 3 , Figure 4 ). The properties of the polymerized products are detailed in Table 3-1, Table 3-2 and Table 3-3.

[0111] Table 3-1

[0112] Table 3-2

[0113] Table 3-3

[0114] (II) Chlorination Experimental Scheme Table 4. Chlorination process parameters

[0115] Before chlorination, the special materials and auxiliary agents are added to the chlorination kettle according to the process parameters shown in Table 4, and stirred with the pre-added hydrochloric acid to form a uniform and stable suspension. Under the precise control of the kettle temperature by the heating and cooling system, chlorine is introduced into the chlorination kettle according to a predetermined procedure, and the chlorination reaction is carried out under the action of the auxiliary agent. After a certain amount of chlorine is introduced, the chlorination reaction ends, and the material begins to cool. After the kettle temperature drops to a certain temperature, the acid water is removed, and the material enters the dryer for drying to obtain the product. The product performance is shown in Table 5.

[0116] Table 5

[0117] From the results in Table 3-1, Table 3-2 and Table 3-3, it can be seen that the bulk density of polyethylene prepared by the catalyst of the present invention in industrial production is increased to 0.46 g / cm 3 , which is very high in high-density polyethylene, and the particle size is more concentrated, with a particle size distribution of less than 0.6, and no large particles or fine powder. This is very suitable for industrial production and reduces production costs. The pore size and pore volume were tested by mercury intrusion, and the pore volume and pore size were 1.33 cm 3 / g and 0.739 m, the pore volume is close to that of the standard sample L0555P, and the pore diameter is much larger than that of L0555P. Such large pore volume and pore diameter are conducive to the diffusion and reaction of chlorine atoms, so the chlorination uniformity prepared by the present invention is good and the chlorination rate is high. From Table 5, the melting enthalpy (J / g) of the chlorinated polyethylene prepared by the present invention is smaller than that of L0555P, which proves that its chlorination uniformity is good.

[0118] From the results in Table 5, it can be seen that the CPE obtained after chlorination, when the chlorine content is 36.5%, all properties have reached the standard of Type A materials, and the product performance can meet the product requirements of Type A materials on the market.

[0119] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a dialkoxy magnesium carrier, characterized in that: The preparation method comprises: in the presence of an initiator, magnesium and alcohol are stirred to react at a temperature T of 30°C ≤ T ≤ 40°C, and the temperature does not need to be increased for aging during the reaction to obtain the dialkoxy magnesium carrier; The alcohol is selected from fatty alcohols represented by the general formula R-OH, where R represents C 1-6 alkyl; The weight ratio of the alcohol to magnesium is (8-30):1; The stirring speed is 600-1500 rpm; The particle size of the dialkoxy magnesium carrier is 3.5-10.0 μm, and the dialkoxy magnesium carrier is spherical or quasi-spherical.

2. The preparation method according to claim 1, characterized in that: The magnesium is magnesium powder with a particle size of 50 to 200 μm; And / or, the initiator is selected from N-chlorosuccinimide, N-bromosuccinimide or I2.

3. The preparation method according to claim 1, characterized in that: The weight ratio of the initiator to magnesium is (0.005-0.3):1; And / or, the reaction time is 3 to 12 hours; And / or, the reaction is carried out under an inert environment.

4. A catalyst, characterized in that The catalyst comprises the dialkoxy magnesium support obtained by the preparation method according to any one of claims 1 to 3; The particle size of the catalyst is 3.0-10.0 μm; and / or the catalyst is spherical or quasi-spherical; And / or, the catalyst is obtained by contact reaction of the dialkoxy magnesium support, the titanium halide compound and the internal electron donor; And / or, in terms of weight percentage, the catalyst contains 20-30 weight % of magnesium, 1-10 weight % of titanium, 5-20 weight % of electron donors and 40-70 weight % of halogen atoms.

5. The method for preparing the catalyst according to claim 4, characterized in that: The preparation method comprises: (1) first reacting the dialkoxy magnesium support and titanium halide in an organic solvent to generate a halogen-substituted alkoxy group of the dialkoxy magnesium; (2) After step (1) is completed, an internal electron donor is added to the system and the temperature is raised to react to obtain the catalyst.

6. The preparation method according to claim 5, characterized in that: The titanium halide is titanium tetrachloride; and / or, relative to 1 mol of dialkoxymagnesium, the amount of the titanium halide is 0.1 to 10 mol; And / or, the organic solvent is selected from C 6-12 aliphatic or aromatic hydrocarbons; And / or, the internal electron donor is an alkoxy silicon compound having a structure shown in Formula I, R’ n Si(OR’’) 4n’ Formula I Wherein, R' and R'' are the same or different and are independently selected from C 1~12 The hydrocarbon group; n and n' are the same or different and are independently selected from natural numbers from 1 to 3; The hydrocarbon group includes alkyl, cycloalkyl, alkenyl, phenyl, alkyloxy, haloalkyl, halocycloalkyl, haloalkenyl, halophenyl, and haloalkyloxy; and / or, relative to 1 mol of magnesium, the amount of the internal electron donor is 0.05 to 1.0 mol; And / or, in step (1), the dialkoxy magnesium support and the organic solvent are first mixed and stirred, cooled to -20 to 10°C, titanium halide is added thereto, and then the temperature is raised to 60 to 80°C; and / or, the temperature when the internal electron donor is added to the system in step (2) is 60-80° C.; And / or, in step (2), the temperature is raised to 100-120° C. and the reaction is carried out for 1-3 hours.

7. A catalyst system, characterized in that The catalyst system comprises: a) the catalyst according to claim 4; b) a co-catalyst, which is an organoaluminum compound R''' 3-m A1X m , where X is halogen and R''' is C 1~12 alkyl.

8. A method for preparing HDPE, characterized in that: The preparation method comprises the steps of: 3~8 The dialkoxy magnesium support obtained by the preparation method according to any one of claims 1 to 3, the catalyst according to claim 4 and / or the catalyst system according to claim 7 are used in the α-olefin polymerization process; The HDPE has one or more of the following parameters: (1) Density: 0.930~0.960g / cm 3 ; (2) Melt mass flow rate MFR5.0 is 0.2 to 2.0 g / 10 min; (3) S value is 10 to 20; (4) Particle size is 100 to 300 microns; (5) Melting point not less than 132°C; (6) Bulk density ≥ 0.36 g / cm 3 ; (7) Particle size distribution (D 90 -D 10 ) / D 50 <0.8; (8) Pore diameter 300-800nm; (9) The content of large-particle powder larger than 425 mm is less than 1 wt%, the content of ultra-fine powder smaller than 63 μm is less than 1 wt%, and the content of powder between 75-425 μm is greater than 98 wt%.

9. A method for preparing CPE, characterized in that: The HDPE obtained by the preparation method of claim 8 is used as raw material.

10. Use of the dialkoxy magnesium support obtained by the preparation method according to any one of claims 1 to 3, the catalyst according to claim 4, or the catalyst system according to claim 7 in the preparation of the HDPE in claim 8 and / or the CPE in claim 9.

Citation Information

Patent Citations

  • Polyethylene catalyst components and their preparation methods

    CN107840914B

  • Polyvinyl resin used for preparing chlorinated polyethylene and preparation method thereof

    CN102432726A

  • Preparation method and applications of alkoxyl magnesium carrier

    CN104356257A

  • Preparation method of spherical magnesium diethoxylate

    CN112299984A

  • Method for regulating and controlling particle size and particle size distribution of ultra-high molecular weight polyethylene

    CN113943386A

Cited By

  • Alkoxy magnesium microsphere carrier and preparation method thereof

    CN121045421A

  • Ethoxy magnesium type titanium slurry polyethylene catalyst and preparation method thereof

    CN121181736A